2020
DOI: 10.1186/s12886-020-01374-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of predictability and influence factors of the achieved lenticule thickness in small incision lenticule extraction

Abstract: Background: To evaluate the differences between the predicted and achieved lenticule thickness (ΔLT) after small incision lenticule extraction (SMILE) surgery and investigate relationships between ΔLT and predicted lenticule thickness in SMILE. Methods: A total of 184 eyes from 184 consecutive patients who underwent SMILE were included in this prospective study. One eye for each patient was randomly selected and included for statistical analysis. To achieve emmetropia, nomogram adds 10% correction of spherical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
12
0
3
Order By: Relevance
“…In previous studies, some researchers have also found that the nomogram was not accurate. Liang et al [ 13 ] suggested adding an 11% correction of SE to the nomogram for SMILE surgery; Zhou et al [ 26 ] adjusted the mean treated SE up to −6.30 ± 2.00 D when the mean preoperative SE was −5.96 ± 1.97 D in SMILE surgery; Fang et al [ 18 ] found that the proportion of overestimation of lenticule thickness in predicted value is 11.9% for ultrasound and about 15% for Pentacam. However, previous studies were only limited to studying the overestimation rate of nomogram and obtained a more accurate estimate value by reducing a certain proportion of nomogram; few studies had constructed a model to predict LT from the major factors affecting LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, some researchers have also found that the nomogram was not accurate. Liang et al [ 13 ] suggested adding an 11% correction of SE to the nomogram for SMILE surgery; Zhou et al [ 26 ] adjusted the mean treated SE up to −6.30 ± 2.00 D when the mean preoperative SE was −5.96 ± 1.97 D in SMILE surgery; Fang et al [ 18 ] found that the proportion of overestimation of lenticule thickness in predicted value is 11.9% for ultrasound and about 15% for Pentacam. However, previous studies were only limited to studying the overestimation rate of nomogram and obtained a more accurate estimate value by reducing a certain proportion of nomogram; few studies had constructed a model to predict LT from the major factors affecting LT.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no comparison with the other algorithms in their study, and this study focused more on reducing the postoperative refractive error than the lenticule thickness error. Fang et al [ 18 ] found that the lenticule thickness predicted by the nomogram exceeds the achieved lenticule thickness by approximately 10%, but it’s just a correction.…”
Section: Introductionmentioning
confidence: 99%
“…First, CCT reduction was overestimated at approximately 23 μm 6 months after SMILE, which was concordant with the results of previous studies. According to several previous studies, CCT reductions could be overestimated at approximately 15–18 μm when examined by Pentacam imaging and approximately 13–24 μm by optical coherence tomography (OCT) after SMILE [ 6 , 9 , 12 , 13 ]. Corneal remodeling pattern was hypothesized as an influencing factor causing the discrepancy between predicted and achieved CCT reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as attempted SE correction increased, more corneal stromal tissues were removed, and stronger corneal stromal expansion strength was observed. In a study evaluating the difference in CCT reduction after SMILE in various degrees of myopia, the deviations were 20.08 ± 6.84 μm and 7.20 ± 10.50 μm in the high and low myopia groups, respectively [ 13 ]. Notably, our study included eyes with myopia more than − 9.0 D, and the deviation was larger than that of the former study, further supporting Reinstein et al’s hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation